Administrative Creativity and Its relationship with Transformational Leadership in Scholastic Sport Activity Directorate in Baghdad from Physical Educators’ Point of View - Shadhan, Falah Hassan; Ali, Ali Abdulatif (Journal of Physical Education, 2021)
The importance of the research lies in creative administration and transformational leadership as new topics that play an integral role in scholastic sport development. The researchers came up with a question that they aim to answer through this researcher: what is the relationship between creative administration and transformational leadership? They used the descriptive method on (250) physical educators in preparatory school. The data was collected and treated using proper statistical operations to conclude that physical educators have the ability to communicate with others and affect others positively. There is a relation between transformational leadership and creativity in physical educators.